(untitled) (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2025)
Drawing on the wide range of work in which they have been involved in multiple cases, discussants presented policies, practices, and contextual realities that inform VPL activities “across continents.”